Pemanfaatan Ekstrak Daun Kemangi (Ocimum basilicum) dalam Pembuatan Handsanitizer Spray Ramah Lingkungan sebagai Antiseptik Alami - Velly Effendi; Della Rosalynna Stiadi (Lembaga Yasin AlSys, 2025)
Concerns arising from the use of synthetic antiseptics in hand sanitizer products have driven efforts to explore safer and more environmentally friendly natural alternatives. This study aims to develop a hand sanitizer spray based on basil leaf extract (Ocimum basilicum) and to evaluate its phytochemical composition, organoleptic properties, pH, homogeneity, and antiseptic efficacy. Three formulations were developed: a control without basil extract (F0), 5% extract (F1), and 10% extract (F2). Basil leaf extract contains flavonoids, tannins, and saponins, which exhibit antibacterial activity, while aloe vera and lime were added as moisturizers, natural fragrances, and supplementary antibacterial agents. Test results showed that all formulations had a pH of 4, conforming to SNI 06-2588 standards, were physically stable with homogeneous mixing, and showed no sedimentation. The highest antibacterial activity was observed in formulation F2, although it was less favored visually due to its color. Formulation F0 was preferred in terms of color and texture, while F2 was superior in aroma. The study concludes that basil leaf extract effectively enhances antibacterial activity in hand sanitizers and holds potential for development as a safe, effective, and eco-friendly natural antiseptic for widespread public use.